2010
DOI: 10.1002/jhm.632
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery dissection (PAD): A very unusual cause of chest pain

Abstract: A 51-year-old African American woman with medical history of essential hypertension and chronic obstructive pulmonary disease (COPD) presented to the hospital with chest pain and shortness of breath. The chest pain was retrosternal and radiated to the back. It lasted for about an hour and resolved without any intervention. After some time, she again felt discomfort in the chest, which was a constant and dull ache.She had similar episodes of chest pain 1 week prior, although less severe in intensity, for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Prior studies have demonstrated that PAD is strongly associated with chronic pulmonary hypertension due to structural cardiac defects, either congenital or acquired [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Chronic pulmonary hypertension results in dilatation of the pulmonary artery trunk, leading to susceptibility to media degeneration and subsequently dissection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that PAD is strongly associated with chronic pulmonary hypertension due to structural cardiac defects, either congenital or acquired [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Chronic pulmonary hypertension results in dilatation of the pulmonary artery trunk, leading to susceptibility to media degeneration and subsequently dissection.…”
Section: Resultsmentioning
confidence: 99%
“…The group of non-CHD associated-PH included idiopathic pulmonary arterial hypertension (19 cases) [ 2 , 22 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], chronic obstructive pulmonary disease (8 cases) [ 1 , 9 , 10 , 37 , [39] , [40] , [41] ], pulmonary hypertension associated with liver disease (4 cases) [ 37 , 42 , 43 ], and pulmonary thromboembolic disease (3 cases) [ 44 , 45 ] ( Fig. 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Medical treatment aims to reduce right ventricle preload and afterload. Medications for reduced pulmonary hypertension, such as endothelin receptor antagonists, phosphodiesterase type 5 inhibitors, and soluble guanylate cyclase stimulants, are helpful 2,4 . No consensus treatment guidelines have been developed, but surgical management or medical management followed by surgery seems to be slightly better than medical management alone 2 …”
Section: Diagnosismentioning
confidence: 99%
“…In most cases the final diagnosis is made only postmortem. The major complications of PA dissection leading to the death of the patient are cardiac tamponade and haemopericardium [1, 2]. Most common acute symptoms include dyspnoea, chest pain, and central cyanosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other rare causes include chronic inflammation of the pulmonary arteries, right heart endocarditis, amyloidosis, trauma, and severe atherosclerosis [6]. In some cases, the cause of pulmonary arterial dissection remains unknown [2, 7]. Pulmonary artery dissection with intimal flap calcification is very rare.…”
Section: Introductionmentioning
confidence: 99%